Strategies in Creating Smart People to Support Tourism Development (Study of the Tongke-Tongke Mangrove Forest Area Community). Issue 1 (September 2021) - Amiruddin,; Surya, Batara; Syafri,; Manaf, Murshal
Abstract: The community is a major component and has an important role in tourism development. The community is required to be able to open up to tourists, and it is to develop themselves with all their potential so that tourism development can be implemented through the encouragement of good institutional capacity of the community, and ultimately through the development of tourism, the community will feel the benefits as a means of improving their economy and quality of life. Therefore, in the tourism area, smart people are needed who can see and utilize every potential and opportunity. This study aims to describe the strategy of creating smart people in the Tongke-Tongke Mangrove forest tourism area, Kab. Sinjai in supporting tourism development. The research was conducted using qualitative descriptive analysis by strengthening observation, interviews, and documentation studies. The results showed that to create smart people in tourism areas, several strategic steps were needed, namely (1) Community involvement in the formulation of tourism development policies, (2) Development of an internet-based area as a medium for communication in business development (3) Assisting production activities and marketing-supported by the existence of a tourism industrial area, (4) Increasing human resources through the empowerment of potential educational backgrounds as well as development, coaching, and training, (5) Fostering the socio-cultural character of the community as capital in their involvement in tourism development. By using these strategies, a smart community will be created and can support the government in developing tourism as part of regional planning and development.